Determinanty i konsekwencje wzrostu poziomu innowacyjności przedsiębiorstw poprzez inwestycje w technologie informacyjne - Bochan, Radosław (Gospodarka w Praktyce i Teorii, 2011)
The development of present economies is determined in the considerable measure through the growth of the level of their informative. Investments in suitable informative technologies imply the development of the economy and raise her competitiveness. The implementation of the services of the type e-bussines, ecommerce, e-work, if e-consulting becomes the key to the economic and social success, both for regions as and the whole country. The changes of the level of the innovations of enterprises exert the huge influence on functioning whole economy, sectors, trades, if individual enterprises. The leadership of the own investigations which will contribute to the creation of unique products, inventions which can abroad be transferred is the most effective way of the enlargement of the innovation. This requires obviously system solutions, which will allow to build suitable legal frames, so the Polish scientifically-investigative potential would not to be distracted and so to the Polish searchingly-developmental centres enlarge can the innovation of different economies in the future.